PRRI/Permesta dalam Pandangan Sejarahwan Dr. RZ Leirissa - La Malihu (Rayhan Intermedia, 2022)
The history of PRRI/Permesta has been written in various forms of scientific work. However, in the view of historian RZ Leirissa, a number of works on PRRI/Permesta tend to be one-sided because they do not pay attention to the perceptions of leaders in turbulent areas. For this reason, Leirissa tries to look at the history of PRRI/Permesta from a more neutral point of view by using the oral history method and a structural approach. From the results of archive data analysis and interviews with a number of leading actors, Leirissa concluded that PRRI/Permesta was not actually a rebellion movement, nor was it merely a central and regional issue, but also related to differences in the concept of development and at the same time civil-military issues. Therefore, according to Leirissa, PRRI/Permesta cannot be equated with DI/TII in West Java and South Sulawesi and RMS in Maluku.